Analisis Kebutuhan Pengembangan Model Pembelajaran Chemistry Real Integrated Laboratory Work (CHEM-RILW) Pada Pembelajaran Kimia - Junaidi, Eka; Anwar , Yunita Arian Sani; Muti'ah, Muti'ah; Idrus, Syarifah Wahidah Al; Hidayanti, Ermia; Purnamasari, Ni Nyoman Dayuni (Chemistry Education Practice, 2025)
This study aims to analyze the need for further development of the CHEM-RILW model, an extension of the previously developed ILW model. The respondents involved in this study included two lecturers (N = 2) and forty-seven chemistry students (N = 47). Data was collected using observation sheets, questionnaires, critical thinking tests, and rubrics for argumentation and communication skills. The results indicated that the implementation of the learning process successfully integrated investigative activities carried out in the laboratory. This integration demonstrated that the pre-laboratory, laboratory, and post-laboratory stages were effectively implemented. However, the previous model did not sufficiently enhance students' interpretation and presentation skills. Additionally, the human element was not adequately emphasized, which limited the development of students' argumentation skills. Analysis of the lecturer questionnaire revealed a need to improve the learning model by incorporating more real-world applications of theory. Based on these findings, it is clear that further development of the ILW model is necessary. The CHEM-RILW model, as an enhancement, introduces real-world aspects and emphasizes the human element in learning, highlighting the relevance of community science in the context of chemistry concepts.